Financial Performance of Islamic Banking in Indonesia with The Maqashid Syariah Index Approach - Pamikatsih, Mutia; Syahputri, Nisrina Anggi; Setiabudhi, Hatta; Sa'diyah, Kholifatus (Ijtimā iyya Journal of Muslim Society Research, 2024)
Banking performance is measured using financial ratios. However, for Islamic banking, it is much more complex compared to conventional banking. It's not just about testing profitability levels; it's more about compliance with Islamic principles, namely Maqashid Shariah. This makes the products and performance evaluation of Islamic banking distinct from conventional banking. The purpose of this research is to assess the financial performance of Islamic Commercial Banks in Indonesia using the Maqashid Shariah Index approach for the period 2017-2019. This research is classified as descriptive quantitative research. The objects of the study are Bank Muamalat Indonesia (BMI), Bank Syariah Mandiri (BSM), Bank Tabungan Pensiun Nasional (BTPN Syariah), and Bank Aceh Syariah (BAS). The research method used the Maqashid Shariah Index analysis technique. The data used are secondary data in the form of annual reports from 2017-2019 obtained from the official websites of each bank. The research results indicate that the financial performance of Islamic Commercial Banks (BUS) using the Maqashid Shariah Index for the period 2017-2019 is as follows: Bank Syariah Mandiri (BSM) achieved the highest ranking with an index value of 0.273841 or 27.38%. The second rank is held by Bank Muamalat with an index value of 0.267941 or 26.79%. The third rank is obtained by Bank Aceh Syariah with an index value of 0.260473 or 26.047%, and BTPN Syariah has the lowest ranking with an index value of 0.1735705 or 17.35%.